Doing a literature search : a comprehensive guide for the social sciences - Hart, Chris (SAGE Publications, 2010)
"Doing a Literature Search provides a practical and comprehensive guide to searching the literature on any topic within the social sciences. The book will enable the reader to search the literature effectively, identifying useful books, articles, statistics and many other sources of information."--BOOK JACKET